Allometry and integration do not strongly constrain beak shape evolution in large‐billed (Corvus macrorhynchos) and carrion crows (Corvus corone). Issue 20 (21st September 2018) - Yamasaki, Takeshi; Aoki, Sou; Tokita, Masayoshi
Abstract: A recent geometric morphometric study on certain landbird lineages revealed that a major part of the variation in beak shape is accounted for by skull size and cranial shape. The study interpreted this result as evidence for the presence of strong evolutionary constraints that severely prevented beak shape from evolving substantially away from predictions of allometry and morphological integration. However, there is another overlooked but similarly plausible explanation for this result: The reason why beak shape does not depart much from predictions might simply be that selection pressures favoring such changes in shape are themselves rare. Here, to evaluate the intensity of evolutionary constraints on avian beak shape more appropriately, we selected large‐billed ( Corvus macrorhynchos ) and carrion crows ( Corvus corone ) as study objects. These landbird species seem to experience selection pressures favoring a departure from an allometric trajectory. A landmark‐based geometric morphometric approach using three‐dimensional reconstructions of CT scan images revealed that only 45.4% of the total shape variation was explained by allometry and beak–braincase integration. This suggests that when a selection pressure acts in a different direction to allometry and integration, avian beak shape can react to it and evolve flexibly. As traditionally considered, evolutionary constraints on avian beak shape might not be all that strong. Abstract : To evaluate the intensity of evolutionary constraints on avian beak shape more appropriately, we analyzed the skulls of large‐billed ( Corvus macrorhynchos ) and carrion crows ( Corvus corone ) based on landmark‐based geometric morphometrics using three‐dimensional reconstructions of CT scan images. Our analyses revealed that only 45.4% of the total shape variation was explained by allometry and beak–braincase integration. This suggests that when a selection pressure acts in a different direction to allometry and integration, avian beak shape can react to it and evolve flexibly despite evolutionary constraints.